Genistein protects against hyperglycemia and fatty liver disease in diet-induced prediabetes mice via activating hepatic insulin signaling pathway - Zhang, Nana; Zhang, Weiyue; Guo, Xinxin; Liu, Jianlin; Li, Shuying; Zhang, Hongtai; Fan, Bei (Frontiers in Nutrition, 2022)
Introduction Insulin signaling via the insulin receptor (IR) may be associated with the amelioration of diet-induced metabolic syndrome. Genistein, a soy isoflavone, has been suggested to play a role in the amelioration of high-fat diet-induced metabolic disorders. Methods Here, we aimed to explore whether genistein regulates glucose and hepatic lipid by activating the insulin signaling pathway in diet-induced obesity mice. Results We showed that treatment of western-style diet-fed mice with genistein (60 mg/kg) significantly improved insulin resistance with decreased hyperglycemia and HOMA-IR index. These effects were linked to activating hepatic IRβ/PI3K/Akt signaling. Furthermore, genistein suppressed gluconeogenesis and promoted glycogen synthesis to maintain glucose homeostasis by increasing the phosphorylation of hepatic FOXO1/GSK3β in vivo and in vitro. The reduced level of insulin and upregulation of insulin signaling in genistein-treated mice also lead to an increase in hepatic energy status by inducing energy-sensing AMPK, reducing hepatic SREBP1c/ACC/FAS without affecting β-oxidation to prevent hepatic lipid accumulation. The protective effect of genistein on hepatic lipid accumulation was also validated in vitro. Besides, genistein had little effect on improvements in intestinal function and liver inflammation. Conclusion Taken together, our results showed that genistein prevents insulin resistance and hyperglycemia through improvements in hepatic function. This study provides new insight into the mechanisms of genistein mediating glucose metabolism and suggests that genistein may be a promising diet ingredient for preventing prediabetes and hepatic lipid accumulation.